2015
DOI: 10.1002/ece3.1380
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐off between thermal tolerance and insecticide resistance in Plutella xylostella

Abstract: Fitness costs associated with resistance to insecticides have been well documented, usually at normal temperature conditions, in many insect species. In this study, using chlorpyrifos-resistant homozygote (RR) and chlorpyrifos-susceptible homozygote (SS) of resistance ace1 allele of Plutella xylostella (DBM), we confirmed firstly that high temperature experience in pupal stage influenced phenotype of wing venation in insecticide-resistant and insecticide-susceptible Plutella xylostella, and SS DBM showed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 64 publications
5
74
0
Order By: Relevance
“…For example, a laboratory study showed that higher temperatures impose a fitness cost on the chlorpyrifos‐resistant strain of the diamondback moth, Plutella xylostella . Under heat stress, the resistant strain of Plutella xylostella has higher rates of wing vein damage and lower survival than the susceptible strain, suggesting a tradeoff between thermotolerance and insecticide resistance . Similarly, in the brown planthopper, Nilaparvata lugens , a chlorpyrifos‐resistant strain is associated with lower fitness compared to its susceptible counterparts at higher temperatures, suggesting that a common genetic mechanism could underlie chlorpyrifos resistance and tradeoffs with thermotolerance in distant species.…”
Section: Climate Change and Insecticide Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, a laboratory study showed that higher temperatures impose a fitness cost on the chlorpyrifos‐resistant strain of the diamondback moth, Plutella xylostella . Under heat stress, the resistant strain of Plutella xylostella has higher rates of wing vein damage and lower survival than the susceptible strain, suggesting a tradeoff between thermotolerance and insecticide resistance . Similarly, in the brown planthopper, Nilaparvata lugens , a chlorpyrifos‐resistant strain is associated with lower fitness compared to its susceptible counterparts at higher temperatures, suggesting that a common genetic mechanism could underlie chlorpyrifos resistance and tradeoffs with thermotolerance in distant species.…”
Section: Climate Change and Insecticide Resistancementioning
confidence: 99%
“…Under heat stress, the resistant strain of Plutella xylostella has higher rates of wing vein damage and lower survival than the susceptible strain, suggesting a tradeoff between thermotolerance and insecticide resistance. 11 Similarly, in the brown planthopper, Nilaparvata lugens, a chlorpyrifos-resistant strain is associated with lower fitness compared to its susceptible counterparts at higher temperatures, 12 suggesting that a common genetic mechanism could underlie chlorpyrifos resistance and tradeoffs with thermotolerance in distant species. The second category is that climatic adaptation will also facilitate the development of insecticide resistance, resulting in an increase in insecticide resistance alleles.…”
Section: Climate Change and Insecticide Resistancementioning
confidence: 99%
“…Although previous studies have been conducted to show the effect of temperature on synthetic insecticides susceptibility, the alteration in entomopathogenic fungi pathogenicity due to changes in temperature was not understood (Deng, Zhang, Wu, Yu, & Wu, ; Garcia et al., ; Lasa, Williams, & Caballero, ; Zhang et al., ). However, susceptibility to entomopathogenic fungi was increased in Las‐infected as compared to uninfected D. citri , but Las infection did not affect the correlation coefficients between temperature and psyllids mortality.…”
Section: Discussionmentioning
confidence: 99%
“…2007), temperature (Zhang et al . 2015) or biotic interactions (Becker & Liess 2015). When fitness costs are context sensitive, the resistance allele frequency may not necessarily decline in the absence of selection.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these factors will be ecological and may exaggerate or conceal pleiotropic effects associated with a resistance allele (Gassmann, Onstad & Pittendrigh 2009); that is, fitness costs may exhibit a degree of context dependence and may increase or only become visible to selection in the presence of additional environmental stressors. For example, fitness costs may be exaggerated by factors such as host plant variety (Bird & Akhurst 2007), parasites and pathogens (Raymond et al 2007), temperature (Zhang et al 2015) or biotic interactions (Becker & Liess 2015). When fitness costs are context sensitive, the resistance allele frequency may not necessarily decline in the absence of selection.…”
Section: Introductionmentioning
confidence: 99%